2022
DOI: 10.3221/igf-esis.63.15
|View full text |Cite
|
Sign up to set email alerts
|

Study of the slant fracture in solid and hollow cylinders: Experimental analysis and numerical prediction

Abstract: This paper is devoted to the numerical and experimental study of ductile fracture in bulk metal forming of the 2017A-T4 aluminum alloy. From an experimental standpoint, the ductile fracture of the 2017A-T4 aluminum alloy is investigated under compressive load. Two cross-sections of solid and hollow specimens are considered. The mechanical behavior and the microstructure of the 2017A-T4 aluminum alloy were characterized. It is found that the well-known barrel shape is obtained when a compressive load is applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The model has been implemented in Abaqus/explicit using the VUMAT user subroutine, including the radial return algorithm to solve the material non-linearity problem [8][9][10]. The numerical integration of the dislocation densities is carried out using the backward/implicit Euler method:…”
Section: Application To a Stainless Steel Tubementioning
confidence: 99%
“…The model has been implemented in Abaqus/explicit using the VUMAT user subroutine, including the radial return algorithm to solve the material non-linearity problem [8][9][10]. The numerical integration of the dislocation densities is carried out using the backward/implicit Euler method:…”
Section: Application To a Stainless Steel Tubementioning
confidence: 99%
“…The corresponding implementation method of the modified Gurson model in shear loading is developed in the ABAQUS/Explicit finite element code, using a user material constitutive subroutine (VUMAT). The implementation of the constitutive law is carried out using the algorithm proposed by Aravas for pressure-dependent plasticity models, which is also based on elastic prediction and plastic correction [39][40][41][42].…”
Section: Shear Effectsmentioning
confidence: 99%
“…The fatigue life of aluminum alloys is sensitive to the loading path, and the load path sensitivity is influenced by a number of factors, such as the material properties, loading conditions, and microstructure. [12][13][14][15] Already in 1970, Miller et al 16 called attention to the effect of strain rate on the cyclic behavior of materials, emphasizing the need for further research on the cyclic stress-strain curve. Woodthorpe et al 17 Many authors have studied the cyclic behavior of aluminum alloys under various conditions such as heat treatments, anisotropy, strain rate, mean strain, and squeeze casting in stress control tests.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some research confirmed that the loading path and heat treatment can have a significant effect on the fatigue life and fracture mode of aluminum alloys. The fatigue life of aluminum alloys is sensitive to the loading path, and the load path sensitivity is influenced by a number of factors, such as the material properties, loading conditions, and microstructure 12–15 …”
Section: Introductionmentioning
confidence: 99%